The Impact Of Supply Chain Flexibility, Agility, Alignment, Adaptability, And Resilience On Ngo Performance Moderated By Organizational Culture - Atieh Ali, Ahmad Ali (2024)
Humanitarian supply chains are processes and networks that aim to provide essential services and goods to organisations and entities in this field. It is considered a fundamental pillar that significantly affects the performance of non-governmental organisations (NGOs). However, some humanitarian supply chains are considered costineffective because they operate in unstable environments and require more funding to achieve necessary humanitarian goals. This study aimed to investigate the impact of the humanitarian supply chain on the performance of NGOs with the moderation of organisational culture. Previous literature on the humanitarian supply chain and the performance of NGOs was reviewed to support the study. The study adopts the Dynamic Capabilities View (DCV) theory the questionnaire was adopted as a tool for this study, as the quantitative approach was used. The study population consisted of directors of relief organizations and supply chain managers in those organizations, and the study sample amounted to 310. The Partial Lease Square - Structural Equation Modeling (PLSSEM) was employed to test the hypotheses. The results of this study show the impact of resilience in the context of humanitarian supply chains on relief organizations in Jordan. Humanitarian organizations need resilience to respond to changing situations. Meanwhile, Organisational culture acts as a strategic asset, influencing the organisation’s effectiveness by shaping people’s behaviour towards it, thereby impacting performance. A notable recommendation from this study is the need for further investigation into the humanitarian supply chain and the performance of NGOs in Jordan. This study stands out as one of the few that shed light on the performance of these organisations in Jordan specifically.